The influence of the liquid layer height on the velocity field and evaporation during local heating; Experimental Heat Transfer; Vol. XX - Misyura S. Ya. Sergey Yakovlevich; Egorov R. I. Roman Igorevich; Morozov V. S. Vasiliy Sergeevich; Zaitsev A. S. Aleksandr Sergeevich (2023, 2023)
Title screen